Legitimacy and Effectiveness as Factors for the Study of Political Wear in Chile Post-Authoritarian. (1990-2014) [Legitimidad y Efectividad Como Factores Para el Estudio del Desgaste Político en Chile Postautoritario. (1990-2014)] - Mella-Polanco, J (Universidad Nacional de Colombia, 2016)
This paper analyzes the structure and evolution of the presidential wear in Chile from 1990-2014, including the governments of Patricio Aylwin (1990-1993), Eduardo Frei RT (1994-1999), Ricardo Lagos (2000-2005), Michelle Bachelet (2006-2009) and Sebastián Piñera (2010-2014). As it is four administrations of the Concertación, and one of the Alianza, our perspective emphasizes the longitudinal study of change in political support, seeking to clarify the importance, for this process, social expectations and perceptions of government performance. For the analysis proposed two annual measurements of the public opinion poll of the Centro de Estudios Públicos (CEP) from 1990-2014 are used. The main objectives of this study are: i) Explain the evolution of the political support of governments in the period 1990-2014, identifying particular features of each government, as well as general patterns, ii) Explain trends and presidential joints wear with In order to identify common cycles of erosion in government support, and iii) analyze the relationship between the change of political support and perceived legitimacy and effectiveness of government. © 2016, Universidad Nacional de Colombia. All rights reserved.